Glycosylated fibronectin point‐of‐care test for diagnosis of pre‐eclampsia in a low‐resource setting: a prospective Southeast Asian population study - Nagalla, SR; Janaki, V; Vijayalakshmi, AR; Chayadevi, K; Pratibha, D; Rao, PV; Sage, KM; Nair‐Schaef, D; Bean, E; Roberts, CT; Gravett, MG (BJOG : an international journal of obstetrics and gynaecology, 2020)
Objective To determine the performance of a glycosylated fibronectin (GlyFn) point‐of‐care (POC) test for pre‐eclampsia (PE) in a large Southeast Asian cohort (India) in comparison to previously described biomarkers. Design A total of 798 pregnant women at ≥20 weeks of gestation were enrolled in a prospective case‐control study. Study participants included 469 normotensive women with urinary mg protein/mmol creatinine ratio <0.3, 135 with PE (hypertension with urinary mg protein/mmol creatinine ratio ≥0.3) and 194 with gestational hypertension (hypertension with urinary mg protein/mmol creatinine ratio <0.3). Methods GlyFn levels were determined using a POC device and PIGF, sFlt‐1 and PAPPA2 levels were determined by immunoassay. Performance was assessed using logistic regression modelling and receiver‐operating characteristic (ROC) curves. Classification performance and positive and negative predictive values are reported at specific thresholds. Results Increased levels of GlyFn, soluble fms‐like tyrosine kinase‐1 (sFlt‐1) and pregnancy‐associated placental protein A2 (PAPPA2), and decreased levels of placental growth factor (PlGF) were significantly associated (P < 0.01) with clinically defined PE. Area under the ROC (AUROC) values with 95% confidence intervals were: GlyFn, 0.99 (0.98–0.99); PlGF, 0.96 (0.94–0.98); sFlt‐1, 0.86 (0.83–0.89); and PAPPA2, 0.96 (0.94–0.97). Of subjects with GH, 48% were positive for more than two PE biomarkers, and 70% of these delivered preterm. Conclusions The Lumella™ GlyFn POC test has been validated in a low/middle‐income country setting for PE diagnosis and may be a useful adjunctive tool for early identification, appropriate triage, and improved outcomes. Tweetable The Lumella™ point‐of‐care test had excellent performance in diagnosing PE in a large Southeast Asian cohort. Tweetable The Lumella™ point‐of‐care test had excellent performance in diagnosing PE in a large Southeast Asian cohort.